Effect of 60Co Gamma Radiation on the Shelf Life of Potato Tubers - Le Doan Dinh Duc, Le Ngoc Trieu, Nguyen Thi Nguyet Ha (2024)
Loss of quality and limits on the storage life of potatoes are very difficult problems for farmers around the world. Farmers normally apply chemicals to minimize the number of aerobic colonies and increase the storage life of potato tubers for year-round supply. However, these methods pose harmful health risks to consumers. This research study evaluates the effect of gamma irradiation, in doses ranging from 0.0 to 1,500 Gy, on the storage life of potatoes at ambient temperature with the aim of optimizing the irradiation dose. The results show that gamma irradiation with 60Co at a dose of 1,000 Gy significantly prolonged the storage life of potatoes to 180 days compared with a control group of nonirradiated potatoes, which had a maximum storage life of 60 days. Nonirradiated potato samples showed maximum sprouting, decay of 44%, and weight loss of approximately 10% after 45 days of storage. Storage duration and radiation treatment influenced potato acidity (pH), although this effect was not deemed significant. Findings indicated that doses of 1,000 Gy can be considered tolerable for consumers because they effectively prolong the shelf life of potatoes, reduce weight loss, and curb decay while maintaining the chemical integrity of the tubers.